Reducing life cycle fossil energy and greenhouse gas emissions for Midwest swine production systems. (10th February 2020) - Tallaksen, Joel; Johnston, Lee; Sharpe, Kirsten; Reese, Michael; Buchanan, Eric
Abstract: Over the last 30 years, the US swine industry has concentrated more animals on fewer farms in the Midwest US corn-belt region to more efficiently produce pork. At the same time, the food industry is beginning to be called upon by consumers to supply products with lower environmental footprints. Swine producers have opportunities to decrease the environmental impacts of their products, but need to know where the most beneficial changes can be incorporated. This study examined the fossil energy consumption and global warming potential (GWP) emissions at Midwestern swine farms using life cycle assessment methodology. Cradle-to-gate swine production scenarios were modeled using a combination of farm productivity survey data and on-farm energy monitoring, with an emphasis on activities related to swine production facilities and their operations. Fossil energy use totaled 10.6 MJ per kg of hog live weight (LW) in the average commercial scenario, 67% of which was used in the grow-finish stage, 11% in the farrowing stage, 12% in the nursery stage, 6% in gestation and 4% in gilt development. Average commercial scenario GWP emissions were 2.41 kg CO2 equiv. per kg hog LW, with 75% emitted during the grow-finish phase, 6% in farrowing, 9% in the nursery phase, 7% in gestation, and 2% in gilt development. Fossil energy required and GWP emissions for facilities and operations were 3.36 MJ and 0.15 kg CO2 per kg hog LW, respectively, and accounted for 32% of the system fossil energy and 6% of emissions in the average commercial scenario. Though fossil energy and GWP impacts resulting from swine production facilities and operations are smaller than those for feed ingredients and manure management, swine producers can directly influence these impacts through management. Heating, cooling, and ventilation are prime areas in facilities and operations where energy efficiency technology could reduce impacts. Lowering facility and operation energy inputs by 30% would decrease fossil fuel use in the system by 10% and slightly decrease GWP emissions. In the future, substituting renewable energy for fossil-based energy and using other efficiency technologies for current electricity and heating fuel needs may be able to eliminate the fossil energy needed for swine facilities and production operations. Highlights: LCA methods examined fossil energy and GWP impacts in Midwest swine production. The study focused on facility and operations impacts using on-farm energy data. Fossil energy and GWP impacts were 10.6 MJ and 2.41 kg CO2 per kg hog LW. Efficiency improvements to facilities could reduce fossil energy use by up to 10%. Swine producers may be willing to implement improvements due to cost savings.